Testing restrictions on a model of Indonesian fish demand - Raja Abdullah, Nik Mustapha; Baharumshah, Ahmad Zubaidi (Penerbit Universiti Kebangsaan Malaysia, 1994)
This paper presents the estimates of the Almost Ideal Demand System (AIDS) analysis for five fish species in Semarang, Indonesia. The results provide the first empirical estimates of own-price and expenditure elasticities of demand of fish species by households. Fish was found to be a necessity good while the tilapia, the freshwater fish species was inferior to other fish species. The tests of demand restrictions results concluded that the preferred demand specification was one with symmetry (and homogeneity) imposed.